How do you subtract (w ^ { 2} + 4w + 4) - ( w + 2)(w2+4w+4)(w+2)?

3 Answers
May 31, 2018

www.nosource.comwww.nosource.com

May 31, 2018

omega = -2ω=2 and -11

Explanation:

As per the question, we have

(omega^2 +4omega + 4) - (omega + 2)(ω2+4ω+4)(ω+2)

And I assume that this is a solvable quadratic equation, f(omega) = 0f(ω)=0

:.(omega^2 +4omega + 4) - (omega + 2) = 0

Opening the brackets, we get

omega^2 +4omega + 4 - omega - 2 = 0

Now as per our Pre-Algebra knowledge

omega^2 + 3omega + 2 = 0

:.(omega + 1)(omega + 2) = 0

:. omega = -1, -2

Hence, the answer.

May 31, 2018

w^2+3w+2

Explanation:

The key here is that we subtract terms with the same degree from each other.

Since there is no other w^2 term, we will just be subtracting

color(blue)(4w-w)

and

color(cyan)(4-2)

Putting it all together, we get

w^2+color(blue)(4w-w)+color(cyan)(4-2)

which simplifies to

w^2+3w+2

Hope this helps!